Pitfalls in Photochemical and Photoelectrochemical Reduction of CO2 to Energy Products - Tomasz Baran; Domenico Caringella; Angela Dibenedetto; Michele Aresta (Molecules)
The photochemical and photoelectrochemical reduction of CO2 is a promising approach for converting carbon dioxide into valuable chemicals (materials) and fuels. A key issue is ensuring the accuracy of experimental results in CO2 reduction reactions (CO2RRs) because of potential sources of false positives. This paper reports the results of investigations on various factors that may contribute to erroneous attribution of reduced-carbon species, including degradation of carbon species contained in photocatalysts, residual contaminants from synthetic procedures, laboratory glassware, environmental exposure, and the operator. The importance of rigorous experimental protocols, including the use of labeled 13CO2 and blank tests, to identify true CO2 reduction products (CO2RPs) accurately is highlighted. Our experimental data (eventually complemented with or compared to literature data) underline the possible sources of errors and, whenever possible, quantify the false positives with respect to the effective conversion of CO2 in clean conditions. This paper clarifies that the incidence of false positives is higher in the preliminary phase of photo-material development when CO2RPs are in the range of a few 10s of μg gcat−1 h−1, reducing its importance when significant conversions of CO2 are performed reaching 10s of mol gcat−1 h−1. This paper suggests procedures for improving the reliability and reproducibility of CO2RR experiments, thus validating such technologies.